THE The relationship between theoria and praxis in ancient philosophy: from socratism to aristotelian theós - Ruiz Moscardó, Francisco Javier (Anales del Seminario de Historia de la Filosofía, 2024)
This paper aims to detail the metaphilosophical conception of Socratism and Aristotelianism, specifying the interrelation between theory and praxis that both projects develop. Starting from a diagnosis common to Michel Foucault and Pierre Hadot, according to which philosophical knowledge was inseparable in ancient times from a “philosophical existence”, it is specified how both Socrates and Aristotle conceived this peculiar “way of life”, concluding that the the roots of the Aristotelian “biós theoretikós” are found in the “examined life” defended by Plato’s teacher. In the course of this research, it also becomes clear that the theoretical dimension of philosophy is a priority for both thinkers, although the discovery of truth, the ultimate purpose of theory, entails practical consequences that are impossible to achieve by any means other than philosophical contemplation. It is resolved, therefore, that the tension between philosophy as “science of truth” and as an “exercise of life” is an essential feature of philosophical work as it was thematized by these two great thinkers.
Keywords: Aristotle; Ancient Philosophy; Foucault; Hadot; Metaphysics; Metaphilosophy